God's Acre in Salem. - (:unkn) unknown (Forsyth County Public Library, 2009)
Photo made in the 1940s.
God's Acre in Salem. God's Acre is the Moravian graveyard. The photo shows preparations for a burial in the graveyard.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth